OP85 Value To Society Of A Nationwide Patient Blood Management Program. (2017) - Brilhante, Dialina; Nunes, António Robalo; Fonseca, Cândida; Mairos, João; Félix, Jorge; Gonçalves, Mafalda; Mota, Melina; Ferreira, Diana; Ferreira, César; Andreozzi, Valeska; Vandewalle, Björn; Rabiais, Sara
Abstract : INTRODUCTION: Patient Blood Management (PBM) describes a multidisciplinary approach that strives to optimize patients own blood and has been reported to reduce blood components utilization while achieving improved patient outcomes and reduced healthcare costs. The aim of this study was to evaluate the public health and economic impact related to the implementation of a nationwide PBM program in Portugal. METHODS: A decision-model comparing two scenarios ("current clinical practice" and "with PBM implementation") was used to estimate the PBM impact including hospital-assisted patients from the following therapeutic areas: surgery (orthopaedic, cardiac and urologic), cardiology, oncology, gastrointestinal bleeding, abnormal uterine bleeding, hemodialysis, inflammatory bowel disease and pregnancy. Model inputs were obtained from Portuguese national health databases and literature review. The public health impact was measured in life years (LY) gained, disability-adjusted life years (DALY) reduction, hospital length of stay (LOS) and 30-day readmission rate reduction. The economic value was expressed in total and hospitalization costs savings. RESULTS: A total of 384, 704 patients were eligible for PBM strategies. We estimated that a one year nationwide PBM implementation could avoid 594 premature deaths, representing a gain of 1, 481 LY and a reduction of 3, 660 DALYs relative to the current paradigm. An 8.4 percent and 37.3 percent reduction in length of stay and 30-day readmission rate are expected, respectively. This corresponds to EUR70.4 million savings in hospitalization costs. Although PBM closer monitoring would imply additional physician visits and medicines use, leading to EUR24.1 million in additional expenditure, in this population the overall PBM implementation can generate net savings of more than EUR67.7 million per year (6.3 percent reduction of public expenditure). CONCLUSIONS: The implementation of a nationwide PBM in Portugal may represent a great public health impact, especially in decreased mortality and disability, with substantial public expenditure reduction.